Genome-wide diversity in temporal and regional populations of the betabaculovirus Erinnyis ello granulovirus (ErelGV) - Anderson F. Brito; Fernando L. Melo; Daniel Mendes Pereira Ardisson-Araújo; W. Sihler; Marlinda Lobo de Souza; Bergmann Morais Ribeiro (2018)
Erinnyis ello granulovirus (ErelGV) is a betabaculovirus infecting caterpillars of the sphingid moth E. ello ello (cassava hornworm), an important pest of cassava crops (Manihot esculenta). In this study, the genome of seven field isolates of the virus ErelGV were deep sequenced and their inter- and intrapopulational sequence diversity were analyzed.No events of gene gain/loss or translocations were observed, and indels were mainly found within highly repetitive regions (direct repeats, drs). A naturally occurring isolate from Northern Brazil (Acre State, an Amazonian region) has shown to be the most diverse population, with a unique pattern of polymorphisms. Overall, non-synonymous substitutions were found all over the seven genomes, with no specific gathering of mutations on hotspot regions. Independently of their sizes, some ORFs have shown higher levels of non-synonymous changes than others. Non-core genes of known functions and structural genes were among the most diverse ones; and as expected, core genes were the least variable genes. We observed remarkable differences on diversity of paralogous genes, as in multiple copies of p10, fgf, and pep. Another important contrast on sequence diversity was found on genes encoding complex subunits and/or involved in the same biological processes, as late expression factors (lefs) and per os infectivity factors (pifs). Interestingly, several polymorphisms in coding regions lie on sequences encoding specific protein domains.By comparing and integrating information about inter- and intrapopulational diversity of viral isolates, we provide a detailed description on how evolution operates on field isolates of a betabaculovirus. Our results revealed that 35-41% of the SNPs of ErelGV lead to amino acid changes (non-synonymous substitutions). Some genes, especially non-core genes of unknown functions, tend to accumulate more mutations, while core genes evolve slowly and are more conserved. Additional studies would be necessary to understand the actual effects of such gene variations on viral infection and fitness.